S35 Treatable traits in symptomatic & untreated children and adults with suspected asthma. (11th November 2022) - Adjei, T; Wang, R; Healy, L; Drake, S; Lowe, L; Bennet, M; Tudge, R; Willmore, L; Kerry, G; Sale, J; Simpson, A; Murray, CS; et al.
Abstract : Background: The concept of treatable traits (TTs) has been applied to severe asthma and chronic obstructive pulmonary disease to facilitate the delivery of precision medicine. We hypothesised that this approach might provide clinical useful insights in patients presenting with symptoms suggestive of asthma. We therefore identified TTs in children and adults with suspected asthma in the RADICA asthma diagnostic study, and investigated any relationship between the prevalence of TTs and symptom control. Methods: Symptomatic and treatment-naïve patients with suspected asthma were recruited. Clinical history and examination were carried out and a wide range of physiological and inflammatory measurements were made. Symptoms were assessed using the Asthma Control Questionnaire, and an asthma diagnosis was confirmed or refuted following 6–8 weeks of inhaled corticosteroids following assessment of all data by an expert panel. Results: Of 172 participants (mean [SD] age 25.9 [16.1] years), 68 (40%) were <18 years old; 59% were female. The prevalence of eczema, gastroesophageal reflux, obesity, cigarette smoke exposure and blood eosinophilia were more common in symptomatic adults than children (p<0.05). Pulmonary TTs were more prevalent in asthma than non-asthma in both children and in adults (p<0.05). In adults only, atopy and current tobacco use were more prevalent in asthmatics and gastroesophageal reflex was more prevalent in non-asthmatics (p<0.05). Breathlessness on exertion was equally prevalent in both asthma and non-asthmatic patients in both adults and children. Obesity, current or former tobacco use and damp in the home were associated with poorer symptom control in adults (p<0.05); there was no association with TTs and symptom control in children. Conclusion: Treatable traits are prevalent in both adults and children with suspected asthma. However, different patterns were observed in those with and without asthma, and distinct TTs were associated with increased symptoms, suggesting that personalised management strategy could be offered to symptomatic patients regardless of diagnostic label. Breathlessness on exertion is unlikely to be a useful symptom in the diagnosis of asthma. Further research is needed for the characterisation of TTs in symptomatic patients with uncertain diagnosis in both adults and children.